Domestic ecologies of gender: Women, material life, and eco-folklore in Saudi proverbs - Ali M. Alshhre (PLoS ONE, 2026)
This article advances an ecocritical reading of women-focused Saudi proverbs as a distinctive form of eco-folklore, where gendered norms are naturalized through domestic material and environmental imaginaries. Analyzing a corpus of 60 proverbs from the Saudi National Encyclopedia’s regional archives, the study integrates feminist critical discourse analysis with material ecocriticism to reveal how proverbial discourse mobilizes everyday objects and processes bread and heat as emblems of maternal care, cooking vessels as symbols of household responsibility, pests like flies and scorpions as metaphors for moral contamination, and adornments such as kohl and henna as mechanisms of reputational surveillance—to position women as the pivotal agents in a gendered domestic ecosystem. The findings highlight an ambivalent moral economy: proverbs ostensibly praising women for motherhood, marital devotion, and “building” the home often reinforce unequal labor and accountability, while cautionary sayings discipline female mobility, visibility, and autonomy through idioms of scarcity, risk, and depletion. By framing Saudi paremiology as vernacular environmental reasoning embedded in gender ideology, this study contributes to Gulf cultural studies, folklore scholarship, and ecofeminist approaches to vernacular knowledge, demonstrating how proverbs function as micro-archives of everyday ecological governance.